THE IMPORTANCE OF THE TRADITIONAL SANDZAK GAMES FOR PHYSICAL EDUCATION IN SCHOOLS - Mersud Koca; Fahrudin Mavrić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Many games have been preserved as a custom, particularly among children, much after the young used to play them. In most of the cases, traditional games represent imitation of the adults' society. Those games are numerous, with an easy start and ending, so the children use them in any possible situation. The implementation of these games and some traditional toys in the nurseries and primary schools in Novi Pazar, has proved our assumptions that teachers has given them positive marks, and even more important is that children are eager to use them and show some interests for their existence. A school can apply various sources within educational process and other out school activities.